The Power Of Positive Thingking - Norman Vincent Peale (New York Faweett Crest, 1956)
Faith in yourself makes good things happen to you. This classic guide to self-esteem and success will help you learn how to: break the worry habit; get other people to like you; avoid "the jitters" in your daily work; believe in yourself and everything yo
Keywords: Psychology - Philosophy Peace of mind -- Religious aspects -- Christianity. Success -- Religious aspects -- Christianity. RELIGION / Spirituality. SELF-HELP / Motivational & Inspirational. SELF-HELP / Personal Growth / Happiness